2022
DOI: 10.1515/ijsl-2021-0079
|View full text |Cite
|
Sign up to set email alerts
|

Unequal English accents, covert accentism and EAL migrants in Australia

Abstract: Accentism refers to the ways that “unequal English accents” become re-allocated in particular English-speaking dominant contexts, creating different presumptions, ideologies and attitudes towards the English accent and pronunciation of English speakers. Using data derived from two larger ethnographic studies, this article aims to explore the ways that English as an Additional Language (EAL) migrants experience covert accentism – the social exclusion caused covertly when the dominant members of society misunder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These effects make it difficult for EAL speakers to cultivate meaningful relationships and assimilate into multicultural environments. Dovchin and Dryden (2022) concluded that covert accentism may negatively impact the cultural, racial, and linguistic identities of EAL migrants, which affirms the significance of understanding how this social exclusion manifests itself in other groups of international migrants, such as students in higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 74%
See 1 more Smart Citation
“…These effects make it difficult for EAL speakers to cultivate meaningful relationships and assimilate into multicultural environments. Dovchin and Dryden (2022) concluded that covert accentism may negatively impact the cultural, racial, and linguistic identities of EAL migrants, which affirms the significance of understanding how this social exclusion manifests itself in other groups of international migrants, such as students in higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 74%
“…In another research project, Dovchin and Dryden (2022) used data from two larger ethnographic studies that contained 150 English as an Additional Language (EAL) participants in Australia, 2 of which were selected for a deeper analysis in Dovchin and Dryden's (2022) study because they provided detailed accounts of covert accentism. Covert accentism is a form of social segregation caused implicitly when dominant members in a given society detect non-native markers in an individual's accent (Applebaum, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Long-standing claims have been made that Australia's successful multicultural society is at risk if migrants fail to integrate and develop proficient English skills. For new migrants, developing proficiency in SAE can help build recognition within society, allowing them to develop a strong sense of belonging (Dovchin, 2022;Dovchin & Dryden, 2022).…”
Section: Language and Migrationmentioning
confidence: 99%
“…Accentism can be understood as a set of ideologies and practices that position the accent of an imagined native English speaker as linguistically superior, thereby justifying the profiling, marginalization, and mistreatment of nonnative English speakers whose accents are deemed inherently inferior (Dovchin and Dryden, 2022; Orelus, 2018). It is important to note that this type of accentism is not created in a vacuum.…”
Section: Theorizing Accentism: From the Interpersonal To The Institut...mentioning
confidence: 99%